Ambiguity aversion and incompleteness of contractual form. - Mukerji, S (American Economic Association, 1998)
Subjective uncertainty is characterized by ambiguity if the decision maker has an imprecise knowledge of the probabilities of payoff-relevant events. In such an instance, subjective beliefs are better represented by a set of probability functions than by a unique probability function.